Two-Photon Fluorescence Probe for Selective Monitoring of Superoxide in Live Cells and Tissues - Chen, Liyan; Cho, Myoung Ki; Wu, Di; Kim, Hwan Myung; Yoon, Juyoung (Analytical Chemistry, 2019)
The abnormal location or generation of superoxide radical anion (O2 •-) are implicated in many diseases, including cancers; thus, development of an efficient method to detect O2 •- is of great importance. Inspired by the fluorophore-governed selective manner to O2 •- and peroxynitrite (ONOO-) of previously reported phosphinate-based fluorescence probes, in this contribution, a phosphinothioate-containing probe, TPP, was designed. The probe exhibited easy accessibility through a one-step sequence and good photostability and biocompatibility. Interestingly, TPP showed high specificity and sensitivity to O2 •- over other reactive oxygen species/nitrogen species including ONOO-. Furthermore, with the assistance of two-photon microscopy, TPP was successfully applied for imaging endogenous O2 •- in live cells and tissues.
Keywords: Fluorescence probes; High specificity; Photo-stability; Reactive oxygen species; Step sequences; Superoxide radical anions; Two photon fluorescence; Two photon microscopy